Immigrant workers and firm resilience on the export market - Léa Marchal; Giulia Sabbadini (Review of World Economics, 2022)
This paper studies whether firms employing immigrant workers are more resilient to an increase in competition in their export markets. Exploiting the surge of Chinese imports following its accession to the World Trade Organization and using a sample of French manufacturing exporters from 2002 to 2015, we find that an increase in the growth rate of Chinese competition in a foreign market has a negative effect on both the two-year survival and growth rate of sales of French exporters on that foreign market. This negative effect on firm performance is mitigated by the employment of immigrant workers.
Keywords: F14; F22; F16; 330; Firm; Heterogeneity; Immigrant workers; Import competition; Productivity